Highly effective gallium arsenide split-disk resonator-based ultrathin metamaterial absorber - Kumar R.; Singh B.K.; Pandey P.C. (My University, 2025)
We present an efficient ultrathin broadband metamaterial (MTM) solar absorber design to enhance the efficiency of solar energy harvesting devices. The simulated MTM absorber consists of only two layers of gallium arsenide and tungsten. The dielectric layer of GaAs is used as a metasurface (resonator) over a ground layer of tungsten. The proposed absorber shows a usual absorbance of 96.57% in the 375 nm to 1200 nm region. We have extracted the complex impedance parameters for computing the absorbance of the absorber. The absorber exhibits polarization-independent behaviours for a wide range of incident angles. We have evaluated the short-circuit current density (J sc) with different incident angles. We have also calculated the absorbance performance at different angles for TE and TM modes. The average absorbance observes approximately 95.41 and 96.88%. Simultaneously we have also calculated the open-circuit voltage (V oc), fill factor (FF) and conversion efficiency (η), whose values are 0.72 V, 84.85% and 27.33%, respectively. The proposed absorber can be utilized as an ultrathin compact solar energy absorber device with efficient solar radiation absorptivity. © 2023, Indian Academy of Sciences.